Zherikhinia matobai sp. nov., a second species of the genus Zherikhinia Alonso-Zarazaga (Coleoptera, Brentidae, Nanophyinae) from the Ryukyu Archipelago, Japan - Yasukawa, Satoshi (Zootaxa, 2023)
Zherikhinia matobai Yasukawa sp. nov., a member of the subfamily Nanophyinae (Coleoptera, Brentidae), is described from the Ryukyu Archipelago, Japan. It is the second species of this genus known. Zherikhinia distylia Alonso-Zarazaga, 1989 and Z. matobai can be easily distinguished by the body color (Z. matobai is reddish-brown and glossy) and the femoral teeth (Z. matobai has one large tooth and a smaller, grain-like tooth).